Trips ماية العلامة التجارية من التزوير والتقليد في ظل اتفاقية تربس - صبري الأرناؤوط, إبراهيم (University of Eloued جامعة الوادي, 2012)
يتناول هذا البحث الوسائل المتعلقة بحماية العلامات التجارية ضد التزوير والتقليد التي وردت في اتفاقية الجوانب المتصلة بالتجارة من حقوق الملكية الفكرية تربس (TRIPS) الدولية لحماية حقوق الملكية الفكرية، وعلى وجه الخصوص إبراز قواعد الإنفاذ الإجرائية والمتضمنة جزاءات مدنية وإدارية وتدابير وقائية وإجراءات جنائية ذات صبغة دولية، والتي يجب على الدول الأعضاء في اتفاقية تربس والمنظمة لمنظمة التجارة العالمية (W.T.O) اتخاذها في مواجهة ظاهرة التزوير والتقليد للعلامات التجارية. ثم بيان موقف الدول العربية من هذه الاتفاقية في كل من الأردن والسعودية. Abstract This research deals with the means for the protection of trade marks against forgery and counterfeiting, which responded to the Convention on Trips (TRIPS) (Agreement on Trade – Related Aspects on Intellectual Property Rights) of the International Protection of Human Intellectual property , and in particular to highlight the enforcement rules of procedure and included civil penalties, administrative and preventive measures and clamp a criminal of an international character, which must be on the member states of The TRIPS Agreement and acceding to the World Trade Organization (W.T.O) to take in the face of the phenomenon of forgery and counterfeiting of trademarks. Then a position of Arab States, of this Convention in both Jordan and Saudi Arabia.
مقال بمجلة البحوث والدراسات
Keywords: علامة تجارية - تزوير - تقليد - اتفاقية التربس